Studi Komparatif Tingkat Value Added Antara Usaha Ternak Sapi Pola Integrasi Dengan Pola Mandiri (Studi Kasus Pada PT. Integrasi Sawit Sapi Batang Hari Dengan Masyarakat Desa Petajen) - Sri Rosmawati; Yaasin Waspodo (Universitas Batanghari Jambi, 2019)
This research is a comparative study between the integration of cattle with independent patterns (Case Study at PT. Batang Sawit Palm Integration with Petajen villagers). The purpose of this research is (1) to find out the cost component of the integration of cattle production patterns at PT Batang Batang Hari Integration with the independent pattern of the Petajen village community. (2) to find out the basic cost of beef cattle production in the integration pattern in PT Batang Hari Cow Integration with the independent pattern of the Petajen village community. (3) to find out the level of value added of cattle integration business pattern in PT Batang Hari Cow Integration with the independent pattern of Petajen village community. The research method used in this research is quantitative descriptive, by looking for a comparison (comparative) between cattle business integration patterns in PT Batang Batang Hari Integration with independent patterns of Petajen village community. From the research results obtained the results of the level of value added (added value) in every sale of one cow in the integration pattern of Rp. 3,187,500, while the level of value added in each sale of one cow in the independent pattern is Rp.1,146,000. The level of value added (value added) in the integration pattern is greater than the level of value added in the independent pattern.